A 4.5 Year‐Long Record of Svalbard Water Vapor Isotopic Composition Documents Winter Air Mass Origin. Issue 23 (4th December 2020) - Leroy‐Dos Santos, C.; Masson‐Delmotte, V.; Casado, M.; Fourré, E.; Steen‐Larsen, H. C.; Maturilli, M.; Orsi, A.; Berchet, A.; Cattani, O.; Minster, B.; Gherardi, J.; Landais, A.
Abstract: From May 2014 to September 2018, a laser spectrometer analyzer provided a 4.5 years continuous record of water vapor isotopic composition at Ny‐Ålesund (8 m above sea level, a.s.l.), Svalbard. It corresponds to the longest data set published in polar regions. A comparison of this data set with a parallel similar data set obtained during 20 days by a second laser spectrometer installed near Mount Zeppelin (474 m a.s.l.) shows that this data set is representative of a regional signal. In addition, the observation of insignificant diurnal cycles in the isotopic signal compared to the strong isotopic signature of synoptic events and the comparison of simultaneous measurements in the vapor and in rain or snow samples lead to the conclusion that our record reflects a large part of the regional dynamics of the atmospheric water cycle driven by large‐scale variability. This study focuses on winters dominated by the occurrence of synoptic events associated with humidity peaks. Using statistics and back trajectories calculations, we link high humidity peaks characterized by an anticorrelation between δ 18 O and d‐excess in the water vapor to a rapid shift of air mass source regions from the Arctic to the North Atlantic Ocean below 60°N. On the other hand, correlation between δ 18 O and d‐excess may be associated with a shift of air mass sources within the Arctic. These results demonstrate the added value of long‐term water vapor isotopic monitoring to better understand the moisture origin in the Arctic and the atmospheric dynamics. Key Points: Svalbard is a key location to study the hydrological cycle and long‐range moisture transport in the Arctic 4.5 years continuous record of water vapor and precipitation isotopic composition at Ny‐Ålesund New isotopic diagnostic to document the origin of air masses at Svalbard